Sistem Dinamik Spasial Untuk Meningkatkan Efektifitas Dan Efisiensi Logistik Pada Rantai Pasok Pangan - Hidayat, Syaiful; Suryani, Erma; Hendrawan, Rully Agus (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2016)
Food security is a cross-cutting issue which has become a national issue as the impact of food insecurity in several regions in Indonesia. Food Logistics Systems focuses on determining the location of the farm, to delivery points and distribution centers of commodities that can improve system performance food logistics. In this case some of the factors considered, commodities, the offender and logistics service provider, Transportation, policies and regulations and food logistics. The integration of SD and GIS (SDS) involved in producing the model output as input for policy formulation in order to improve the effectiveness and efficiency of logistics in the food supply chain. The results of the dynamic system model scenario will be visualized using GIS as a basis for decision-making related to increasing the effectiveness and efficiency of logistics in the food supply chain, so as to enhance the competitiveness and sustainability of food logistics in the future.